2012
DOI: 10.3856/vol40-issue4-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of microphytoplankton biomass in the lower reaches of the Biobío River and the adjacent coastal area off Central Chile during autumn winter conditions

Abstract: ABSTRACT. The Biobío River in central Chile is the third largest watershed and second largest river in Chile in terms of discharge volume. Three sampling campaigns were made in the lower reaches of the river and the adjacent coastal ocean to evaluate the influence of the river plume on the physical/chemical conditions and the abundance/biomass of microphytoplankton during autumn-winter conditions. In addition, a preliminary quantification of riverine nutrients, dissolved silica, and phytoplankton carbon flux t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, recent studies have suggested changes in the upwelling versus nonupwelling cycle at Concepcion Bay (~36.5ºS) due to the key role of river discharge in coastal systems (Testa et al 2018). In this bay high nutrient concentrations have been described along the year associated to Itata river input and coastal upwelling activity with peaks in winter and spring, respectively (Léniz et al 2012, Anabalón et al 2016.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, recent studies have suggested changes in the upwelling versus nonupwelling cycle at Concepcion Bay (~36.5ºS) due to the key role of river discharge in coastal systems (Testa et al 2018). In this bay high nutrient concentrations have been described along the year associated to Itata river input and coastal upwelling activity with peaks in winter and spring, respectively (Léniz et al 2012, Anabalón et al 2016.…”
Section: Discussionmentioning
confidence: 98%
“…These changes are not related to river discharge as seen in other coastal upwelling systems, (e.g., California/Oregon, NW Iberian-Portugal coasts), or even in central-south Humboldt area. In those areas, freshwater input leads to changes in phytoplankton structure, biomass (Chl-a) and PP (Warrick et al 2005, Silva et al 2009, Iriarte et al 2012, Léniz et al 2012, Testa et al 2018, Aparicio-Rizzo & Masotti 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In upwelling areas of the Chilean coast, river discharges can also modify oceanographic conditions and nutrient export (Léniz et al 2012, Pérez et al 2015, Masotti et al 2018. Thus, previous studies have shown that an increase in river flow changes salinity and the exportation of nutrients (Pérez et al 2015, Masotti et al 2018.…”
Section: Meteorological Hydrological Data and Upwelling Indexmentioning
confidence: 99%
“…In this region, recent studies have shown evidences of the impact of the nutrient export in these river plumes on the carbon biogeochemistry and phytoplankton community of coastal waters off Central Chile in winter (Iriarte et al, 2012;Léniz et al, 2012;Pérez et al, 2015;Yevenes et al, 2016) and its possible contribution in maintaining high primary productivity rates in coastal waters (Testa et al, 2018). Nonetheless, there is a lack of a systematic analysis into the regional scale influence of the river discharges variability on nutrient loading and phytoplankton biomass in coastal waters.…”
Section: Introductionmentioning
confidence: 99%